Prebiotic effects of cucurbitaceae fruits using in-vitro fermentation by gut microbiota and development of granola bars and their effects in humans - Azid, Saffanah Mohd Ab (2023)
Inflammatory Bowel Disease (IBD) is prevalence in Western countries and has remained over years, and the disease has been rapidly increasing in Asian countries including Malaysia. The present study was to investigate the prebiotic activities of Cucurbitaceae plants using in vitro fermentation by gut microbiota. The nutritional profile and physicochemical characterization of each freeze-dried pumpkin powder (FDPP), winter melon powder (FDWMP) and rock melon powder (FDRMP), and their formulation products; granola bars of winter melon (GBWM) namely GBWM control, GBWM + 4% inulin, GBWM + 8% inulin and GB of inulin 4%, respectively, were investigated. The prebiotic properties of all freeze-dried samples were evaluated on the growth promoting of probiotics Lactobacillus plantarum TISTR 1465 and Bifidobacterium lactis BB12. The prebiotic activity of these samples through in vitro fermentation using batch culture, Fluorescent in situ Hybridization (FISH), prebiotic index (PI) score, and production of short chain fatty acids (SCFAs) as fermentation end products were evaluated. The prebiotic effects of 4 formulations of GBWM fortified with different concentrations of inulin were investigated among healthy subjects who consumed a daily 25 g granola bars and their faecal samples were collected at different time points. The microbial diversity and defecation behaviour via in vivo studies were examined. The growth of L. plantarum TISTR 1465 was observed in the FDWMP while FDRMP in B. lactis BB12. The growth of Bifidobacterial has significantly increased (P > 0.05) from 0 hour and 72 hours for D glucose and FDWMP, however, the increase of population was not significant for inulin, FDPP and FDRMP. The number of Lactobacili significantly increased at 6 hours for FDPP and 24 hours for FDWMP and FDRMP. The prebiotic index of D glucose, inulin, FDPP, FDWMP and FDRMP were 1.33, 1.50, 1.75, 1.90 and 1.44. Both acetic and propionic acid were the main SCFAs produced. The lowest moisture content (3.60%) was detected in GBWM + 8% inulin, highest in ash content (1.96%) was monitored in GBWM control. The highest protein (8.51%) was recorded in GBWM + 4% inulin, whereas the highest in total dietary fibre (27.56 g) was discovered in GBWM + 8% inulin. The overall acceptance of sensory evaluation showed that the GBWM control was more preferred over other formulations. The value of hardness of GBWM control is the lowest or softer compared to other formulations fortified with inulin. For genus profile, both Bifidobacterial and Lactobacillus were discovered in all formulations except for GBWM control due to presence of inulin. The frequency of defecation (1 time/day) and (more than 1 time/day) were increased after consumption of GBWM control and GBWM + 4% inulin, respectively. The frequency of defecation time was increased after consumption from all formulations except for GBWM + 4% inulin. The type of faeces (Type 4 normal) among subjects was increased after consumption of all formulations. The colour of faeces (Brown) was increased after consumption from all formulations except for GBWM control. The amount of stool per defecation time (1-2 stools) after consumption of GBWM control was increased from 50% to 100%. In overall, the usage of FDWMP in granola bars resulted in increment of ash, protein, and total dietary fibre, improvement of regularity of defecation behaviour, and well accepted by panellists.